La funcionalidad de los elementos del arte folklórico y la mitificación del poder socio-cultural del indio en la narrativa de José María Arguedas - Príncipe Cotillo, Guillermo (2023)
The aim of the study was to analyze the role of folk art -music, singing, dance and musical instruments- and the socio-cultural power of the Indian in the narrative production of José María Arguedas. The approach -within the jargon of research typification that has been used- corresponded to the qualitative analysis of the information sources. For its development, the theoretical presuppositions of the literary hermeneutic methodology were used (Galván, l. 2008: 11), in its levels of analysis, interpretation and critical explanation. As a result, it has been verified that the Andean reality is a heterogeneous and contradictory contest, personalized by an alarming social inequality between two manifestly opposed forces: that of the boss and the legendary resistance of the Indian. The two coexist on the same stage but marked by an antagonistic social relationship: the boss as dominant and the Indian as dominated or subjugated. Faced with this situation, the Indian has as a counterpart a strength that is as powerful as or more powerful than that of the patron: his ancestral and millennial artistic culture, embodied in the passionate practice of music, song, dance, musical instruments, as well as his performers who, impregnated with the mythical forces of nature -hills, lagoons, rivers, birds, the cosmos or simple objects, such as the zumbayllu- are metaphorically associated in the power, also mythical of the Indian, as if to impose itself on the pattern. This being the case, the function of music or folk art is therefore to rescue, prospectively, the mythical “hidden” power that the Indian possesses, not only to impose himself on the boss but also perhaps to bet on the rupture of the differentiating barrier that separates them.